# calculus

posted by .

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?

B) So once that is found, then how can you prove that if 0(<or=)u(<or=)v(<or=)10, then 0(<or=)sqrt(u+1)(<or=)sqrt(v+1)(<or=)10?

* calculus - Damon, Saturday, April 3, 2010 at 3:35pm

How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
===========================
does the square root increase (is the derivative positive) as x goes from 0 to 10 ?
If so the left side of the domain is minimum and the right side is maximum of the function and we only need to test the ends.

d (x+1)^.5 / dx = .5 /sqrt(x+1)
that is positive everywhere in the domain so all we have to prove is the end points.

0 </= x </= 10

if x = 0
sqrt x+1 = sqrt 1 = 1
if x = 10
sqrt x+1 = sqrt 11 = 3.32

so
1 </ sqrt(x+1) </= 3.32

* calculus - Damon, Saturday, April 3, 2010 at 3:37pm

for part b again the derivative is positive throughout the domain so if v is right of u then sqrt (1+v) > sqrt(1+u)

* calculus - Sarita, Saturday, April 3, 2010 at 5:52pm

thank you!

C) They give a recursively defined sequence: a_1=0.3; a_(n+1)=sqrt((a_n)+1)for n>1
How do you find out the first five terms for it. then prove that this sequence converges. What is a specific theorem that will guarantee convergence, along with the algebraic results of parts A and B?

* calculus - Damon, Saturday, April 3, 2010 at 7:26pm

.3
sqrt 1.3 = 1.14
sqrt 2.14 = 1.46
sqrt 2.46 = 1.57
sqrt 2.57 = 1.60

hmmm, not getting bigger very fast.
let's see what happens to the derivative for large n
.5/sqrt(x+1)
ah ha, look at that. When n gets big, the derivative goes to zero. So the function stops changing.

* calculus - Sarita, Sunday, April 4, 2010 at 1:05pm

But why would you look for the derivative to go to zero? Does it have to do anything with the theorem: If summation of a_n converges then limit_(n-->infinity) of a_n = 0. If so, what would the limit be approaching? 10 or infinity? But if not, then what theorem would we use? I know you explained about the larger n for the derivative, but I do not understand how that relates to one of the theorems.

* calculus - Sarita, Sunday, April 4, 2010 at 1:21pm

But doesn't it converge to infinity and not 0?

* calculus - Sarita, Sunday, April 4, 2010 at 1:22pm

we want it to converge to 0 right? But does it even converge if it goes to infinity, or is that divergence?

* calculus - Sarita, Sunday, April 4, 2010 at 2:28pm

Do you do the limit on the derivative?

Or is there another way to prove convergence with a theorem of some sort?

• calculus -

Look at the sequence of 6 that we did. The number is getting closer and closer to 1.6 about. We are not looking at the sum of a series. We are looking at terms in a sequence. If they do not change for large n, they converged. They do not have to converge to zero. They just have to stop changing. Only their change (the derivative) must be zero for convergence.

• calculus -

Which theorem, together with the results of parts a and b, will guarantee convergence?

Would it be the convergent sequences are bounded theorem, where if {a_n} converges, then {a_n} is bounded,

or

would it be the bounded monotonic sequences converge theorem, where 1) if {a_n} is increasing and a_n(</=)M for all n, then {a_n} converges and lim_(n-->infinity)a_n(</=)M, and 2) if {a_n} is decreasing and a_n(>/=)m for all n, then {a_n} converges and lim_(n-->infinity)a_n(>/=)m?

or

is there another one?

• calculus -

Sure, that will do.

• calculus -

So, what would be the exact limit of the sequence defined in part c? But it says to square the recursive equation and take limits using some limit theorems. How do you do that?

## Similar Questions

l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
2. ### Calculus

Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
3. ### Math/Calculus

Solve the initial-value problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else?
4. ### calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
5. ### Calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
6. ### calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
7. ### calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
8. ### calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
9. ### calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
10. ### calculus

prove that d/dx 4x .√(x + √x) = 6x+5 (x)1/2/√(x + √x) solution is d/dx 4x.[x+(x)1/2]1/2 = d/dx 4x.[x+(x)^1/2]^1/2 d/dx 4x.[x+(x)^1/2]^1/2 Product Rule = 4x[1/2(x+(x)^1/2)^-1/2 * (1+1/2x^-1/2) +[x+(x)^1/2]^1/2*4 …

More Similar Questions